A 10-year (2010-2019) scientometrics assessment of Iranian and Turkish scholarly outputs based on Scopus database - Nadi-Ravandi, Somayyeh; Batooli , Zahra (Malaysian Journal of Library and Information Science, 2022)
This study sought to compare scientific trends in research performance of Iranian and Turkish scholarly outputs based on 15 metrics in four categories This study is an analytical and applied study based on scientometrics indices and based on SciVal Tool. The findings showed that Iranian researchers' performance was better than Turkish researchers in metrics such as scholarly outputs, citation count, citations per publication, citedness rate, Field-Weighted Citation Impact, and views count, views per publication, Field-Weighted Views Impact, collaboration and top journal percentiles during the period. However, Turkish researchers had better performance than Iranian academics in collaboration and academic-corporate collaboration impact. Based on the research results, policymakers in Iran should take steps to remove obstacles to the international cooperation. Besides, this comparison shows that Iranian researchers should seek a greater perspective for competition. The most important issue is that despite the increase in the quantity of research, Iran should consider measures to increase their research quality and impact on industry and people's lives as well. Increasing the relationship between industry and academic institutes can contribute to this impact. In this study, while comparing all research outputs of Iran and Turkey based on 15 SciVal indicators, a comprehensive study has been conducted on the reasons for Iran's scientific growth, discussed in the discussion section, which can be the approach and plan of many research policy makers in other countries.